The Multifarious Endophytic Actinobacterial Isolate, Streptomyces tubercidicus UAE1, Combined With the Seaweed Biostimulant Further Promotes Growth of Avicennia marina - Alkaabi, Ameera K.; Ramadan, Gaber A.; Elddin, Afraa M. Taj; El-Tarabily, Khaled A.; AbuQamar, Synan F. (Frontiers in Marine Science, 2022)
Mangrove (Avicennia marina) is a “green lung” tree growing along the Arabian Gulf coastline in the United Arab Emirates. Here, we aimed to determine the impact of the application of a commercial seaweed extract (SWE) biostimulant and endophytic actinobacterial isolates on growth performance and endogenous hormonal levels of mangroves. Therefore, we isolated endophytic plant growth-promoting (PGP) actinobacteria (PGPA) from mangrove roots and evaluated their potential as biological inoculants on mangrove seedlings under greenhouse and open-field nursery conditions. Seven salt-tolerant isolates had the ability to produce different levels of in vitro plant growth regulators (PGRs) and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (ACCD) and to solubilize phosphorus. Accordingly, only one isolate, Streptomyces tubercidicus UAE1 (St), was selected based on its relative superiority in displaying multiple modes of action and in successfully colonizing mangrove tissues for 15 weeks. In the greenhouse experiments, plants treated with St and SWE significantly (p < 0.05) improved dry biomass by 40.2% and 55.1% in roots and 42.2% and 55.4% in shoots, respectively, compared to seawater-irrigated non-treated mangrove plants (control). However, St+SWE caused a greater significant (p < 0.05) increase in dry weight of roots (67.6%) and shoots (65.7%) than did control plants. Following the combined treatment of St+SWE, in planta PGR levels were found to be greatly enhanced over the non-treated control plants grown in non-SWE supplemented sediments, or plants inoculated with only St without the supplementation with SWE, or with non-inoculated plants grown in sediments supplied with SWE only. This was evident from the significant (p < 0.05) increases in the photosynthetic pigments and production of PGRs, as well as the reduction in the endogenous ACC levels of plant tissues compared to those in other treatments. Tissue nutrient contents of seedlings also increased by at least two-fold in St+SWE treatment as compared to control. Similar effects were observed on all growth parameters under natural open-field nursery conditions. Combining St with SWE not only stimulates plant growth but also potentially has additive effects on mangrove ecosystem productivity in nutrient-impoverished soils in the Arabian coastal areas. This report is the first in the field of marine agriculture that uses SWE as a nutrient base for actinobacteria capable of producing PGRs and ACCD.